2015
DOI: 10.1111/bjd.14230
|View full text |Cite|
|
Sign up to set email alerts
|

Pyoderma gangrenosum and pregnancy: an example of abnormal inflammation and challenging treatment

Abstract: Pyoderma gangrenosum (PG) is a neutrophil-predominant inflammatory disease that initially presents as a sterile pustule and may progress to ulcerations. Its root cause is unknown, but the presentation is commonly associated with systemic inflammatory conditions such as inflammatory bowel disease, arthritis and haematological abnormalities. On the other hand, pregnant women show a progressive neutrophilia during gestation, which culminates in a major inflammatory event to help drive labour. Although uncommonly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 90 publications
2
36
0
Order By: Relevance
“…A recently published review article described 26 cases of pyoderma gangrenosum during pregnancy. The authors proposed progressive neutrophilia, which occurs during normal pregnancy and reaches its peak in the second and third trimester, as potential trigger factor [ 5 ] .…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…A recently published review article described 26 cases of pyoderma gangrenosum during pregnancy. The authors proposed progressive neutrophilia, which occurs during normal pregnancy and reaches its peak in the second and third trimester, as potential trigger factor [ 5 ] .…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Pyoderma gangrenosum (PG) is a type of neutrophilic dermatosis that shows noninfectious ulcers characterized by neutrophil infiltration of the skin 1 . PG is frequently associated with systemic diseases such as inflammatory bowel disease, rheumatoid arthritis, and hematologic disorders 2 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, pregnancy‐associated pyoderma gangrenosum is rare and tends to affect women in their second and third trimesters. Steele et al . reviewed 26 cases with pregnancy‐associated pyoderma gangrenosum, including nine patients (34.6%) with prior episodes of pyoderma gangrenosum or wound dehiscence, and 12 patients (46.1%) with pyoderma gangrenosum lesions that developed at the site of cesarean sections between 1 day and 4 weeks after delivery.…”
mentioning
confidence: 99%
“…They suggested that alterations in the immune system during pregnancy, such as progressive neutrophilia, a placenta‐derived granulocyte colony‐stimulating factor, and the balance shifting toward Th1 and Th17 at the end of pregnancy, might predispose certain patients to pyoderma gangrenosum. In normal pregnancy, the placenta stimulates granulopoiesis through the release of granulocyte colony‐stimulating factor, leading to an increased number of neutrophils. Neutrophils exposed to pregnancy hormones promote the establishment of maternal tolerance through the induction of a population of CD4 + T cells that are both regulatory and proangiogenic .…”
mentioning
confidence: 99%
See 1 more Smart Citation